The Legal Rule: Between Regulation and Obligation - Sadoon, Ayad Kadhim; Yaghi, Akram Hassan (Journal of Economic, Administrative and Legal Sciences, 2025)
This research aims to clarify the concept of the legal rule, its binding nature on the individuals it addresses, and how it differs from other rules such as moral and religious rules, relying on both inductive and analytical methodologies. The importance of the legal rule lies in its association with sanction and obligation to ensure compliance. Therefore, this research focuses on three main aspects: the nature and characteristics of the legal rule, including its general, social, abstract, and binding nature, along with its connection to legal sanction; the classification of legal rules based on obligation, distinguishing between imperative and supplementary rules as well as flexible and rigid rules; and finally, the relationship between the legal rule and sanction and its impact on compliance. The research concludes with several findings, the most significant of which is that legal rules are essential for regulating society and derive their strength from their obligatory nature, enforced through the sanctions they entail.